Solving Internal Communication Challenges in Tourism and Hospitality Enterprises in Three Northern European Countries - Luka, Ineta (Journal of Education Culture and Society, 2024)
Aim. The aim of the research is to analyse goals, practices, and challenges of internal organisational communication in tourism and hospitality enterprises and offer teaching/learning methodologies to further smooth internal organisational communication. Methods. Twelve semi-structured expert interviews to analyse organisational communication from various aspects were conducted with top level management representatives in 2020–2023. The data was analysed applying content analysis. The themes elicited were grouped into three contextual categories to conduct in-depth analysis. Additionally, SWOT analysis was conducted. Results. The findings indicate that the main goals of internal organisational communication depend on the type of the company. E-mail is the most frequently used written communication channel by tourism companies. WhatsApp or FB group is equally popular among all companies. Face-to-face communication remains the preferred oral internal communication channel in all businesses, regardless of the company location and size. Conclusion. The challenges discovered in the research may be addressed through non-formal and informal learning activities derived from real-life situations and problems to engage adult learners in active, participatory learning encouraging them to collaborate and contribute to the common organisational goals and shared values. Practical application. The suggestions on teaching/learning methodologies to improve internal organisational communication may be practically applied in workplace learning as well as in teaching/learning languages in formal and non-formal adult education. Cognitive value. The article provides an analysis of how adult learners’ communication skills may be developed by incorporating Natural Approach of language learning, Cooperative Learning and game-based learning to secure contextualised participatory learning to improve internal organisational communication.